Wired/Wireless Internet Communications 7th International Conference, WWIC 2009, Enschede, The Netherlands, May 27-29, 2009. Proceedings - Berg, Hans van den.; Heijenk, Geert; Osipov, Evgeny; Staehle, Dirk.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the 7th International Conference on Wired/Wireless Internet Communications, WWIC 2009, held in Enschede, The Netherlands in May 2008. The 13 revised full papers were carefully reviewed and selected from 39 submissions. The papers are organized in topical sessions on energy efficient WSN design, routing & transport protocols for WSNs, security and protocol design and mobility & handover management. .
Energy Efficient WSN Design -- A Novel MAC Protocol for Event-Based Wireless Sensor Networks: Improving the Collective QoS -- Implicit Sleep Mode Determination in Power Management of Event-Driven Deeply Embedded Systems -- On Prolonging Sensornode Gateway Lifetime by Adapting Its Duty Cycle -- Routing and Transport Protocols for WSNs -- Routing and Aggregation Strategies for Contour Map Applications in Sensor Networks -- Path-Based Reputation System for MANET Routing -- Hop-to-Hop Reliability in IP-Based Wireless Sensor Networks - A Cross-Layer Approach -- Security and Protocol Design -- A Scalable Security Framework for Reliable AmI Applications Based on Untrusted Sensors -- The Quest for Mobility Models to Analyse Security in Mobile Ad Hoc Networks -- RDTN: An Agile DTN Research Platform and Bundle Protocol Agent -- Mobility and Handover Management -- Realization Aspects of Multi-Radio Management Based on IEEE 802.21 -- Seamless Mobility of Senders Transmitting Multi-user Sessions over Heterogeneous Networks -- An Adaptive Optimized RTO Algorithm for Multi-homed Wireless Environments -- Handover Incentives for WLANs with Overlapping Coverage.
Keywords: Computer science; Computer communication systems; Software engineering; Computer security; Computers; Electrical engineering; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Systems and Communication Service; Software Engineering; Systems and Data Security; Communications Engineering, Networks; Electronic books